2014
DOI: 10.1080/01495739.2014.914776
|View full text |Cite
|
Sign up to set email alerts
|

On a Theory of Thermoelastic Materials with a Double Porosity Structure

Abstract: Abstract. In this paper we use the Nunziato-Cowin theory of materials with voids to derive a theory of thermoelastic solids which have a double porosity structure. The new theory is not based on the Darcy's law. In the case of equilibrium, in contrast with the classical theory of elastic materials with double porosity, the porosity structure of the body is influenced by the displacement field. We prove the uniqueness of solutions by means of the logarithmic convexity arguments as well as the instability of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 26 publications
(37 reference statements)
0
81
0
Order By: Relevance
“…For Case 2, the thermal attenuation peak moved to the seismic band and the thermal wave is more wave‐like at these frequencies. Kumar et al (), based on the theory of Iesan and Quintanilla (), predict negative quality factors of the P wave, in this case, at the whole frequency range, despite the fact that the latter authors have shown the uniqueness of solutions as well as their stability when the internal energy is positive definite. Our attenuation factor is positive over all frequencies.…”
Section: Physics and Simulationsmentioning
confidence: 91%
See 1 more Smart Citation
“…For Case 2, the thermal attenuation peak moved to the seismic band and the thermal wave is more wave‐like at these frequencies. Kumar et al (), based on the theory of Iesan and Quintanilla (), predict negative quality factors of the P wave, in this case, at the whole frequency range, despite the fact that the latter authors have shown the uniqueness of solutions as well as their stability when the internal energy is positive definite. Our attenuation factor is positive over all frequencies.…”
Section: Physics and Simulationsmentioning
confidence: 91%
“…Iesan and Quintanilla () derive a theory of porothermoelasticity, based on a double porosity structure. This theory is not based on Biot equations and Darcy law, so that it is not directly comparable with ours.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, on the basis of balance of equilibrated force the theories of elasticity and thermoelasticity for materials with a double porosity structure are presented by Ieşan and Quintanilla [19]. The basic threedimensional BVPs of the equilibrium theory of elasticity for materials with a double porosity structure are investigated by using the potential method (boundary integral equation method) and the theory of singular integral equations by Ieşan [18].…”
Section: Introductionmentioning
confidence: 99%
“…Following Iesan and Quintanilla [42], the field equations and the constitutive relations for a homogeneous thermoelastic material with double porosity structure, when the Hall current is taken into account, can be written as: T T 0  , a superposed dot represents differentiation with respect to time variable t.…”
Section: Basic Equationsmentioning
confidence: 99%